The bright and dark side of autonomy: How autonomy support and thwarting relate to student motivation and academic functioning - Johansen, Marius O.; Eliassen, Sigrunn; Jeno, Lucas M. (Frontiers in Education, 2023)
According to Self-Determination Theory, autonomy support is essential in fostering optimal learning, growth, and functioning among students across all levels. In contrast, autonomy thwarting is associated with student malfunctioning. The purpose of the current study was to investigate the relationship between perceptions of autonomy support and thwarting, students’ autonomous and controlled motivations, and aspects of student functioning in a higher education setting. The sample consisted of 414 Norwegian university students recruited from introductory calculus courses. Structural equation modelling showed that perceived autonomy support predicts autonomous motivation, and negatively linked to controlled motivation. Autonomy thwarting negatively predicts autonomous motivation and positively controlled motivation. We found that autonomous motivation positively predicts engagement, effort, and learning, while controlled motivation negatively predicts vitality, engagement, and positively predicts effort. The results are in line with the tenets of Self-Determination Theory, and the present study highlights the importance of autonomy support during lectures and the need for instructors to avoid creating autonomy thwarting situations for students.